PENGARUH ACADEMIC RESILIENCE DAN MOTIVASI BELAJAR TERHADAP SELF REGULATION SISWA SEKOLAH DASAR - Iqlimaw Wardani; Prof. Dr. Hj. Darmiany, M.Pd; Dr. Ida Ermiana, M.Pd (STKIP Subang, 2025)
This study aims to examine the influence of academic resilience and motivation on students’ self-regulation in elementary school. The study employed a quantitative approach with an ex post facto design. A total of 56 students participated as respondents, and data were collected using a validated and reliable Likert-scale questionnaire. Data were analyzed using multiple linear regression. The results indicate that academic resilience has a significant effect on self-regulation, while motivation does not show a significant effect. Simultaneously, both variables significantly influence self-regulation, although their contribution is relatively low, as indicated by an R Square value of 0.147. These findings suggest that academic resilience plays a crucial role in shaping students’ self-regulation, whereas motivation does not contribute meaningfully within the context of this study. The study recommends strengthening students’ academic resilience through adaptive learning strategies and supportive learning environments